Elements of Social History of Popular Song in Algeria. Texts And Contexts - Hadj MILIANI (Turath, 2023)
One of the peculiarities of music and songs in Algeria is that of having aroused very little interest in their origins, their use and their formal characteristics for native chroniclers and scholars before French colonization.